2004
DOI: 10.1007/s00420-003-0486-x
|View full text |Cite
|
Sign up to set email alerts
|

Segmental nerve conduction velocity in vibration-exposed shipyard workers

Abstract: Reduced SNCV in the digits may be a consequence of industrial exposure to vibration. Each sensory nerve segment appeared to have a different characteristic velocity and different pattern of association with skin temperature. There are differences between median and ulnar nerve segments, with potentially important consequences when standard distances are used to assess wrist-digit velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Several investigators have also described a distal pattern of delayed sensory nerve conduction velocity (SNCV), localized to the digits (Sakakibara et al 1994(Sakakibara et al , 1998Hirata et al 2002). The methodology and our results from a baseline study of segmental SNCV in vibration-exposed shipyard workers were the Wrst phase of an international exposure-response study on HAV, and were previously reported in this journal (Cherniack et al 2004a) and seemed to conWrm the earlier reports. SigniWcant digital SNCV reduction was observed.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…Several investigators have also described a distal pattern of delayed sensory nerve conduction velocity (SNCV), localized to the digits (Sakakibara et al 1994(Sakakibara et al , 1998Hirata et al 2002). The methodology and our results from a baseline study of segmental SNCV in vibration-exposed shipyard workers were the Wrst phase of an international exposure-response study on HAV, and were previously reported in this journal (Cherniack et al 2004a) and seemed to conWrm the earlier reports. SigniWcant digital SNCV reduction was observed.…”
Section: Introductionsupporting
confidence: 84%
“…In 2001, the IUG and the larger exposed group (EG) were demographically similar in age and years of employment (Cherniack et al 2004a). However, as Table 2 demonstrates, the nine subjects from the IUG who were tested in 2001, but had dropped out in 2004 (column 2), were signiWcantly older by 7.36 years than those who were tested in 2001 and retested in 2004 (column 3).…”
Section: Internal Comparisonsmentioning
confidence: 97%
See 3 more Smart Citations